2008
DOI: 10.1080/01612840701748714
|View full text |Cite
|
Sign up to set email alerts
|

Tactful Monitoring: How Thai Caregivers Manage Their Relative with Schizophrenia at Home

Abstract: Approximately 343,680 individuals in Thailand suffering from schizophrenia are cared for at home by relatives, most of whom have a little knowledge of the disease; therefore they're left to develop their own strategies of care. Data were collected by in-depth interviews and observation involving 17 caregivers of relatives diagnosed with schizophrenia. Data were analyzed using the constant-comparative method of grounded theory. Caregivers' chief concern was avoiding psychotic episodes. They do this through a pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 22 publications
3
18
0
Order By: Relevance
“…Mokgothu et al (2015) also found that families use calming techniques, creative communication and praise as strengths. These findings are confirmed by Swink (2010) and Dangdomyouth, Stern, Oumtanee and Yunibhand (2008) who report that families use calm attitudes and respect as strengths in their communication with mentally ill family members.…”
Section: Maintaining a Calm Attitude Towards The Mentally Ill Family supporting
confidence: 78%
“…Mokgothu et al (2015) also found that families use calming techniques, creative communication and praise as strengths. These findings are confirmed by Swink (2010) and Dangdomyouth, Stern, Oumtanee and Yunibhand (2008) who report that families use calm attitudes and respect as strengths in their communication with mentally ill family members.…”
Section: Maintaining a Calm Attitude Towards The Mentally Ill Family supporting
confidence: 78%
“…Incorporating improved self-care strategies for family caregivers is also needed to address the impact of their own chronic health problems. Two intervention programs that may have potential for Thai family caregivers are based on respite and creating dedicated social spaces for the chronically mentally ill (Dangdomyouth et al, 2008).…”
Section: Implications For Practice and Nursing Educationmentioning
confidence: 99%
“…With the global move towards community-based care, most individuals with schizophrenia are being cared for by their families in the community. In Thailand, approximately 343,680 individuals with schizophrenia are cared for at home by their relatives (Dangdomyouth et al, 2008). Thai family members caring for individuals with schizophrenia are reported to experience significant stress and burden of care (Pipatananond et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Primary caregivers are not sure about, and do not know if there are, any strategies that will be able to help their patients, however, after they are educated by psychiatric nurses about the causes of schizophrenia, they both understand and believe the information. They try to collaborate and coordinate with health professionals in order to provide good care for people with schizophrenia (Dangdomyouth, Stern, Oumtanee, & Yunibhand, 2008;Kertchok et al, 2011;Petcharat, 2004;Lueponglukkana, 1992).…”
Section: Introductionmentioning
confidence: 98%
“…A study conducted in Thailand (Dangdomyouth et al, 2008) found that the process of tactful monitoring has been employed by family caregivers in caring for persons with schizophrenia. The process has shown that the caregivers take their role of caring for their ill family members to be keeping an eye on their behavior, checking and reminding them of their medication intake, asking about symptoms, preventing the intake of strong beverages and helping their patients do daily activities with the guidance of psychiatric nurses.…”
Section: Introductionmentioning
confidence: 99%